Evaluation of temperament and some slaughter traits of Hungarian Merino ram lambs - Pajor, Ferenc; Szentléleki, Andrea; Tőzsér, János; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
Twenty-seven Hungarian Merino ram lambs with 55 days of age and 17.9 kg of weight were lot-fed on a concentrate mix for 40 days then they were slaughtered. The lambs were fed ad libitum mixture of grain and concentrate. Temperament score test: behaviour of animals was assessed in a 5-score system while weighing, spending 30 sec on the scale. Before slaughtering, fat thickness of Hungarian Merino ram lambs was in vivo estimated between the 12th and 13th rib by ultrasound measurements (Falco 100 device, linear probe, 18 cm, wave-length: 3.5 MHz, depth: 7.5 cm). After slaughtering, the warm carcass weight and longissimus dorsi area were measured for the ram lambs. The correlation of the temperament scores were negative with the corresponding weight at end of the trial (rrank = -0.50, P < 0.01), warm carcass weight (rrank = -0.57, P < 0.01) and longissimus dorsi area (rrank = -0.75, P < 0.001), as well. Furthermore, it was found positive correlation between temperament scores and fat thickness (rrank = 0.55, P < 0.01). The lambs with good temperament had higher weight at end of the trial (27.41 kg), warm carcass weight (13.70 kg ), longissimus dorsi area (20.05 cm2), and lower fat thickness (0.13 cm), than lambs having average and poor temperament (23.2 kg, 11.18 kg, P < 0.05; 14.10 cm2, 0.21 cm, P < 0.01).